Inclusion of Mannan-oligosaccharide and a-Tocopherol in the Diet: Their Effect on Growth Performance and Carcass Characteristics of Broiler Chicken - Sinha, Pallavi; Kumar, Sanjay; Kumar, Kaushalendra; moni, Chandra; Singh, P. K; Kumar, Deepak; Kumar, Pramod; Kumari, Jyoti (Indian Journal of Animal Nutrition, 2017)
The present experiment was conducted to evaluate the effect of supplementing prebiotic mannan-oligosaccharide (MOS) and a-tocopherol individually and in combination on the performance and carcass characteristics of broiler chicken. A total of 240, day-old Vencobb broiler chicks of either sex were randomly assigned to four dietary treatment groups with three replicates of 20 birds for 7 weeks. The chicks in all the groups were fed with the starter and finisher ration as per BIS recommendations, however, in treatments T2, T3 and T4, the chicks were also provided with a-tocopherol @ 400 IU, mannan-oligosaccharide @ 0.4% anda-tocopherol @ 400 IU + mannan-oligosaccharide @ 0.4% of the feed, respectively. The basal diet served as treatment T1. There was significant (P